Election type and the logic of pre-election violence: Evidence from Zimbabwe. (April 2023) - Daxecker, Ursula; Rauschenbach, Mascha
Abstract: Election violence is often conceptualized as a form of coercive campaigning, but the literature has not fully explored how electoral institutions shape incentives for competition and violence. We argue that the logic of subnational electoral competition – and with it incentives for violence – differs in presidential and legislative elections. In presidential elections, national-level considerations dominate incentives for violence. Presidential elections are usually decided by winning a majority of votes in a single, national district, incentivizing parties to demobilize voters with violence in strongholds. In contrast, election violence is subject to district-level incentives in legislative elections. District-level incentives imply that parties focus on winning the majority of districts, and therefore center violent campaigning on the most competitive districts. We test our argument with georeferenced, constituency-level data from Zimbabwe, a case that fits our scope conditions of holding competitive elections, violence by the incumbent, and majoritarian electoral rule. We find that most violence takes place in strongholds in presidential elections, especially in opposition strongholds. In contrast, competitive constituencies are targeted in legislative contests.